E-polis: etyczne dylematy GTI w domenie totarientalności - Olbromski, Cezary (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2009)
The author undertakes to the contemporary global economic transformation and the universal middle class being shy this pcess (the notion of the ‘middle class’ is not used in its classic meaning here, and it rather refers to the largest group of people who are well-settled in the e-civilization). In his opinion, this universal middle class is not a homogenous group. He also emphasizes the profound role of the ethical level represented by making up a TIG (Topic Information Group – a group whose task is to col- lect and store the information which is civilizationally significant and has the properties of scarce resources).
E-polis: the ethical dilemmas of GTI in the totarientality domain